2020
DOI: 10.1002/jmv.26622
|View full text |Cite
|
Sign up to set email alerts
|

Possible vertical transmission and antibodies against SARS‐CoV‐2 among infants born to mothers with COVID‐19: A living systematic review

Abstract: Current evidence suggests that coronavirus disease 2019 (COVID‐19), caused by severe respiratory syndrome coronavirus 2 (SARS‐CoV‐2), is predominantly transmitted from human‐to‐human. However, evidence on vertical transmission and natural passive immunity among the newborns exposed to COVID‐19 is scanty and varies. This poses a challenge on preventive interventions for the newborns. We conducted a systematic review to first, determine the likelihood of vertical transmission among COVID‐19 exposed infants and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 58 publications
3
58
1
4
Order By: Relevance
“…A more recent systematic review (n = 205 infants of COVID-positive mothers) found that while vertical transmission of COVID-19 is unlikely, antibodies against SARS-CoV-2 were found in 10/11 (90%) infants who were tested. 28 As pregnant women are more susceptible than the general population to respiratory pathogens including COVID-19, maternal infection and inflammation in response to the virus could affect the developing fetus and even postnatal life. With the continuing pandemic of COVID-19, there is general consensus further studies are warranted to investigate pregnant women with COVID-19, follow-up the pregnancy outcomes, and monitor postnatal development of the fetus.…”
Section: Maternal-fetal and Perinatal Transmissionmentioning
confidence: 99%
“…A more recent systematic review (n = 205 infants of COVID-positive mothers) found that while vertical transmission of COVID-19 is unlikely, antibodies against SARS-CoV-2 were found in 10/11 (90%) infants who were tested. 28 As pregnant women are more susceptible than the general population to respiratory pathogens including COVID-19, maternal infection and inflammation in response to the virus could affect the developing fetus and even postnatal life. With the continuing pandemic of COVID-19, there is general consensus further studies are warranted to investigate pregnant women with COVID-19, follow-up the pregnancy outcomes, and monitor postnatal development of the fetus.…”
Section: Maternal-fetal and Perinatal Transmissionmentioning
confidence: 99%
“…Several meta-analyses of case reports with small cohort sizes have been performed in order to gain clarity on the overall incidence of SARS-CoV-2 vertical transmission, estimating rates ranging from 3 to 8% [ 19 , 61 , 62 ]. However, the criteria for vertical transmission in theses analyses were not as strict as proposed in Shah et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these negative practices are: 1) women being forced to go through labor and birth without the presence of a partner or support person (34,35), 2) some NICUs not allowing any parental presence at the bedside while others are limiting either the amount of time that the parents can visit or allowing only one parent to be present at a time (36), 3) some hospitals continue to separate mothers who are COVID-19 positive or a Person Under Investigation (PUI) from their infants despite WHO recommendations to avoid this practice (37), 4) discouragement of skin to skin contact and direct breastfeeding (38), 5) early discharge following birth, as early 24 h post-birth for vaginal births and 48 h post-cesarean birth (39, 40), 6) a lack of access to in person pediatric follow-up and hands-on technical breastfeeding assistance (2). Indeed, during the initial phase of the pandemic in Italy, there was concern that breastfeeding had actually been implicated as a "culprit or scapegoat, " despite available evidence suggesting that 1) few pregnant women have been severely affected by COVID-19, 2) evidence for transplacental transmission of the virus very rarely shows a clinical impact, and 3) infected neonates are generally asymptomatic, or have few symptoms, with similar infection rates with vaginal delivery or Cesarean section (41,42).…”
Section: Impact Of the Covid-19 Pandemic On Breastfeeding Mothersmentioning
confidence: 99%
“…Given the extensively documented benefits of human milk and breastfeeding for mothers, infants, the society, and the environment (3,54), as well as the low likelihood of infants becoming ill from COVID-19 (41,42), this is an opportunity for health care professionals to undertake a call to action to protect human milk and breastfeeding. Since no live virus has been detected in human milk whereas specific antibodies against SARS-CoV-2 have (18,23,24), a claim that cannot be attributed to infant formula, health care providers should use the current pandemic to underscore the importance of human milk and breastfeeding as a health promoting and possibly lifesaving medical intervention (55).…”
Section: Call To Action To Protect Human Milk and Breastfeedingmentioning
confidence: 99%